The Cyclical Behavior of Strategic Inventories - Rotemberg, Julio J.; Saloner, Garth (Quarterly Journal of Economics, 1989)
This paper presents a model in which inventories are used by a duopoly to deter deviations from an implicitly collusive arrangement. Higher inventories allow firms to punish cheaters more strongly and can thus help to maintain collusion. We show that when demand is high, the incentive to deviate increases so that increases in inventories may be optimal for the duopoly. This rationalizes the observed positive correlation between inventories and sales. In our empirical section we show that, as our model predicts, this correlation is more important in concentrated industries. We also provide several examples where inventories have been a factor in cartel behavior.